Applying of gas analysis in diagnostic of liver diseases - K. I. Chuikova; Yu. V. Kistenev; S. S. Gomboeva (Бюллетень сибирской медицины)
This review covers the major works devoted to analysis of gas excretions of patients with liver diseases, the possibility of early diagnosis and monitoring of these patients on basis of their gas excretion analysis are discussed. Noninvasiveness of methods of gas analysis allows considering them as perspective and valuable for diagnostics in clinical proceeding.